Awareness and Process:: The Role of the European Union Peace II Fund and the International Fund for Ireland in Building the Peace Dividend in Northern Ireland - Matic, Mislav; Byrne, Sean; Fissuh, Eyob (Journal of Conflict Studies, 2007)
ABSTRACT The role of the European Union (EU) Peace II Fund and the International Fund for Ireland (IFI) in building the peace dividend in Northern Ireland is examined through the perspectives of community groups, funding agencies, local strategic partnerships, civil servants, and development officers. The findings presented in this article explore the role of economic assistance in building peace in Northern Ireland through a public opinion survey of 1,023 citizens and by examining the perceptions of 98 participants from Northern Ireland, the Border Area, and Dublin with direct experience of the protracted ethnopolitical conflict and the role of international funding assistance. The focus of this article is to evaluate the dimensions of ‘awareness’ and ‘process’ in the funding application process for both the EU Peace II Fund and IFI Fund.